Cytogenetic damage in peripheral blood cultures of Chaetophractus villosus exposed in vivo to a glyphosate formulation (Roundup) - Rossi, Luis Francisco (2018)
Different concentrations of a glyphosate formulation, Roundup® Full II (66.2% glyphosate) were tested in culture peripheral blood of armadillo Chaetophractus villosus with cytogenetic biomarkers like mitotic index (MI), chromosomal aberrations (CA), sister chromatid exchange (SCE) and cell proliferation kinetics (CPK) by means of replication index. Adults animals of both sexes were exposed to RU at four concentrations ranging from 0.026 mL RU solution to 0.379 mL RU daily in oral treatment with the same volume (0.2 mL) during 7 days. We analyzed the induced damage at different times considering T0 as control value, one (T1), seven (T7) and 30 days (T30). One day after, only the higher concentration shows MI significant differences (p < 0.05), at T7 the frequency increases and at T30 it decreases reaching T0 values. The analysis of CA frequencies shows that only 0.106 mL RU/day exhibit significant differences vs T0 values. A great variability is expressed in the values of standard deviation (SD) and in the wide confidence intervals of the media. One day after treatments (T1) all four concentrations shows significant differences in SCE vs T0 values. Replication Index (RI) does not show significant differences. The dose-response behavior was not observed in either CA or SCE. The consistency of the findings obtained with the same biomarkers in vitro support the idea of expanding studies in order to characterize the risk doses for these mammals.